Postmodern rendition of myth in Ashbery’s ‘Syringa’ - Farsi, Roghayeh; Nowroozi, Sima (Acta Scientiarum. Language and Culture, 2022)
Postmodern poetry revisits the traditions and subjects myth and history to drastic experimentations. The present paper reacts to Ashbery’s postmodern rendition of the myth of Orpheus in his poem ‘Syringa’ (Ashbery, 1985). He dismantles and opposes the myth of Orpheus and Eurydice and disrupts its totalitarian voice. The main concerns of the paper are to investigate what linguistic potentials Ashbery deploys in his experimentation, how these potentials help him appropriate and then subvert the mythical subtext, and what the consequences of this subversion could be. He disturbs the myth of Orpheus by drawing on the potentials of constructed oppositions. These potentials help Ashbery deconstruct the mythical narrative and adapt it to his postmodern tastes. The theoretical framework comprises Leslie Jeffries’s notion of constructed opposition. The methodology is analytic and interpretive; it conducts a close reading of the poem which situates the poem at the intersecting nodes of myth, poetry, and language. The poem is argued to have relied heavily on the oppositions that Ashbery sets up between his text and its mythical subtext. The paper concludes negation and shifts of verb-tenses are the main structural triggers of opposition along with semantic triggers.